Repair bond strength of a resin composite to alumina-reinforced feldspathic ceramic - Goia, Tamiye Simone; Pereira Leite, Fabiola Pessoa; Valandro, Luiz Felipe; Oezcan, Mutlu; Bottino, Marco Antonio (Quintessence Publishing Co Inc, 2006)
This study compared the microtensile bond strength of a repair resin to an alumina-reinforced feldspathic ceramic (Vitadur-alpha, Vita) after 3 surface conditioning methods: Group 1, etching with 9.6% hydrofluoric acid for 1 minute plus rinsing and drying, followed by application of silane for 5 minutes; group 2, airborne particle abrasion with 110-mm aluminum oxide using a chairside air-abrasion device followed by silane application for 5 minutes; group 3, chairside tribochemical silica coating with 30-mu m SiOx followed by silane application for 5 minutes (N = 30). Group 1 presented the highest mean bond strength (19.7 +/- 3.8 MPa), which was significantly higher than those of groups 2 (10 +/- 2.6 MPa) and 3 (10.4 +/- 4 MPa) (P <.01). Scanning electron microscope analysis of the failure modes demonstrated predominantly mixed types of failures, with adhesive and/or cohesive failures in all experimental groups.